Significance, Plight and Strategy of Eco-Civilization Cultivation in Colleges and Universities for the New Era - Lin Xue, Liujing Yao, Shaojie Chen, Jialin Gao, Haibo Wang (Forest Chemicals Review, 1970)
Colleges and universities undertake the important tasks of talent fostering, scientific research, cultural inheritance and innovation, and service for the society. In the new era ahead, eco-civilization cultivation is a requisite for colleges and universities to promote eco-civilization construction and to create a harmonious campus. By building an indicator system for evaluating satisfaction with eco-civilization cultivation services in colleges and universities, which comprises 4 primary indicators (understanding of eco-civilization, satisfaction with textbooks, satisfaction with teachers, and satisfaction with eco-education activities) and 16 secondary indicators, this study has singled out 6 universities in Fuzhou as the research subjects, and harnessed grey relational analysis to dig into the difficulties faced by colleges and universities in promoting eco-civilization cultivation and the underlying causes. In response to the government's realistic concerns over eco-civilization construction and the pressing need to achieve sustainable socioeconomic development, colleges and universities must effect a fundamental shift in the goals of eco-civilization cultivation, innovate both the education carriers and the collaborative promotion model, and bolster the revival and expansion of eco-civilization cultivation in colleges and universities with a fresh approach.